Designing a knowledge-based tourism information system. (2nd September 2008) - Noel, Laurence; Carloni, Olivier; Moreau, Nicolas; Weiser, Stephanie
The goal of the Eiffel project is to design a knowledge-based information system that can be used by tourism organisations, both, to manage their resources and to promote them on a web portal. In this paper, we define and analyse two types of processes: first, the integration of data into the knowledge-base (internalisation process) and second, the communication of data from the knowledge base on a web portal (externalisation process). We describe how knowledge acquisition techniques and inference services can be used to alleviate tourism experts' annotation tasks and control the validity of the data imported into the knowledge base. Then, we analyse how semantic data can be used to provide targeted information and interactions so as to improve exploratory search on the web portal.